2022
DOI: 10.1093/europace/euac185
|View full text |Cite
|
Sign up to set email alerts
|

Same-day discharge after transvenous lead extraction: feasibility and outcomes

Abstract: Aims Same-day discharge (SDD) is safe for patients undergoing electrophysiology procedures. There is no existing data regarding SDD for patients undergoing transvenous lead extraction (TLE). We report our experience with SDD for patients undergoing TLE. Methods and results The study group included patients undergoing TLE between February 2020 and July 2021 without an infectious indication. A modified SDD protocol for device i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…| 285 feasibility of SDD for TLE. 4,5 More specifically, in this cohort, we found that the only significant predictor of SDD remains a procedure end-time before 12:00. This does not confirm the findings of Dagher et al, which identified a higher procedure complexity (more extracted leads, with longer dwell times, using more advanced tools and techniques) as a predictor of overnight stay.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…| 285 feasibility of SDD for TLE. 4,5 More specifically, in this cohort, we found that the only significant predictor of SDD remains a procedure end-time before 12:00. This does not confirm the findings of Dagher et al, which identified a higher procedure complexity (more extracted leads, with longer dwell times, using more advanced tools and techniques) as a predictor of overnight stay.…”
Section: Discussionmentioning
confidence: 54%
“…4,5 In their case series, Atteya et al described the characteristics and outcomes of 22 patients who were discharged the same day following TLE for a noninfectious indication, with no reported 30-day procedure-or device-related complications. 4 In their case-control study of patients undergoing elective TLE for a noninfectious indication, Dagher et al compared those who were discharged the same day (n = 80) with those who stayed overnight due to the occurrence of immediate procedure-related complications (n = 31), confirming the safety of an SDD approach, with no reported major procedure-related complications. 5 Our study adds to the existing body of knowledge, because it is the first one evaluating the safety of SDD in patients following uncomplicated TLE (i.e., patients with immediate complications were not included) for any indication (i.e., patients with an infectious indication were included).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, SDD was strongly considered when patients had good social support, the procedure was not deemed complicated, postprocedure recovery was smooth, and when no minor or major complications were seen. Attaya et al 17 reported safe outcomes of SDD after TLE in patients who met pre‐specified criteria, including early procedure time, no need for anticoagulation, physician judgment, and patient social situation.…”
mentioning
confidence: 99%
“…Of note, SDD was strongly considered when patients had good social support, the procedure was not deemed complicated, postprocedure recovery was smooth, and when no minor or major complications were seen. Attaya et al 17 SDD allows for better healthcare utilization and saves costs in an environment where hospitals suffer from financial constraints and are constantly operating at near-maximal capacity. 18 These two factors were further magnified during the COVID-19 pandemic when preserving hospital resources for people who need it most became of paramount importance.…”
mentioning
confidence: 99%